Implikasi Omnibus Law Terhadap Hak Konstitusional Atas Lingkungan Hidup Yang Sehat - Ahmad Gelora Mahardika (The Constitutional Court of the Republic of Indonesia, 2021)
One of the goals of the formation of the omnibus law is to increase the index of ease of doing business in Indonesia, which is currently far behind other countries. One effort that was then carried out by the government was to cut down a number of permits, one of which was an environmental permit, namely the obligation to complete EIA and UKL-UPL documents. However, this regulation is actually contradictory to the spirit of sustainable development (SDGs) which development must be in line with environmental protection. The action also has the potential to violate Article 28H paragraph (1) of the 1945 Constitution which requires the state to ensure the protection of citizens' constitutional rights to a clean and healthy environment. Especially in countries that have the highest business ease indexes, such as Denmark, South Korea and the United States, the issuance of EIA documents is mandatory and is carried out strictly. Therefore this article will try to look at the implications of the omnibus law for citizens' constitutional rights to a clean and healthy environment.